Leading educational establishments in pandemic times: some certainties among the uncertainties (Innovaciones Educativas, 2020)
Amidst the uncertainty created by the pandemics in 2020, schools’ headteachers have had to continue leading their schools. Despite this, some certainties about leadership in troubling times emerged. Among them: the relevance of understanding the nature of inconstant contexts, leaders’ adaptability; promoting distributed leadership practices, developing flexibility, and caring about both the staff and community’s welfare.
Keywords: Leadership; pandemics; headteachers; school administration; educational administration; COVID-19